Reduction of Physical Activity Levels During the COVID-19 Pandemic Might Negatively Disturb Sleep Pattern - Diniz, Tiego A.; Christofaro, Diego G. D.; Tebar, William R.; Cucato, Gabriel G.; Botero, João Paulo; Correia, Marilia Almeida; Ritti-Dias, Raphael M.; Lofrano-Prado, Mara C.; Prado, Wagner L. (Frontiers in Psychology, 2020)
Background: The outbreak of novel coronavirus disease 2019 (COVID-19) has been caused a global panic and public concern due its mortality ratio and lack of treatments/vaccines. Reduced levels of physical activity has been reported during the outbreak, affecting the normal daily pattern. Objective: To investigate (i) the relationship of physical activity level with sleep quality, and (ii) the effects of reduction physical activity levels on sleep quality. Methods: A Google form was used to address personal information, COVID-19 personal care, physical activity and mental health of 1907 adult volunteers. Binary logistic regression was used to verify the association of physical activity parameters and sleep quality. Results: Insufficient physical activity levels were a risk factor to have disturbed sleep pattern (OR: 1.30, 95%CI [1.03-1.64]), however, when the BMI was added to the analysis, there was no ore statistical difference (OR: 1.26, 95%CI [0.99-1.60]). On the hand, we found that the reduction of physical activity levels was associated with negative changes in sleep quality (OR: 1.72, 95%CI [1.37-2.17]), regardless all the confounders (OR: 1.53, 95%CI [1.20-1.95]). Conclusion: Disruption in daily physical activity routine, rather than physical activity level, negatively influence sleep quality.